Comparative Analysis of Transcriptomes in Rhizophoraceae Provides Insights into the Origin and Adaptive Evolution of Mangrove Plants in Intertidal Environments - Guo, Wuxia; Wu, Haidan; Zhang, Zhang; Yang, Chao; Hu, Ling; Shi, Xianggang; Jian, Shuguang; Shi, Suhua; Huang, Yelin (Frontiers in Plant Science, 2017)
Mangroves are woody plants that grow at the interface between land and sea in tropical and subtropical latitudes, where they exist in conditions of high salinity, extreme tides, strong winds, high temperatures, and muddy, anaerobic soils. Rhizophoraceae is a key mangrove family, with highly developed morphological and physiological adaptations to extreme conditions. It is an ideal system for the study of the origin and adaptive evolution of mangrove plants. In this study, we characterized and comprehensively compared the transcriptomes of four mangrove species, from all four mangrove genera, as well as their closest terrestrial relative in Rhizophoraceae, using RNA-Seq. We obtained 41,936–48,845 unigenes with N50 values of 982–1,185 bp and 61.42–69.48% annotated for the five species in Rhizophoraceae. Orthology annotations of Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, and Clusters of Orthologous Groups revealed overall similarities in the transcriptome profiles among the five species, whereas enrichment analysis identified remarkable genomic characteristics that are conserved across the four mangrove species but differ from their terrestrial relative. Based on 1,816 identified orthologs, phylogeny analysis and divergence time estimation revealed a single origin for mangrove species in Rhizophoraceae, which diverged from the terrestrial lineage approximately 56.4 million years ago (Mya), suggesting that the transgression during the Paleocene–Eocene Thermal Maximum may have been responsible for the entry of the mangrove lineage of Rhizophoraceae into intertidal environments. Evidence showed that the ancestor of Rhizophoraceae may have experienced a whole genome duplication event approximately 74.6 Mya, which may have increased the adaptability and survival chances of Rhizophoraceae during and following the Cretaceous–Tertiary extinction. The analysis of positive selection identified 10 positively selected genes from the ancestor branch of Rhizophoraceae mangroves, which were mainly associated with stress response, embryo development and regulation of gene expression. Positive selection of these genes may be crucial for increasing the capability of stress tolerance (i.e., defense against salt and oxidative stress) and development of adaptive traits (i.e., vivipary) of Rhizophoraceae mangroves, and thus plays an important role in their adaptation to the stressful intertidal environments.